2011
DOI: 10.1097/id.0b013e3182096979
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of the Effect of Using Growth Hormone Around Immediate Dental Implants in Fresh Extraction Sockets: An Experimental Study

Abstract: The use of GH powder around dental implants placed immediately in fresh extraction sockets enhanced periimplant bone response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(11 reference statements)
0
4
0
3
Order By: Relevance
“…Previous published studies available in the literature have reported that systemic administration of GH enhances the healing of bone fractures in the tibia and femur [10,11] and in calvarial defects in rats [1]. In addition, some studies have shown that local application of GH (either topical or irrigation), may also promote a direct and specific effect on bone tissues that seems to stimulate both bone deposition and the osseointegration of implants [3,4,16,17,18,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous published studies available in the literature have reported that systemic administration of GH enhances the healing of bone fractures in the tibia and femur [10,11] and in calvarial defects in rats [1]. In addition, some studies have shown that local application of GH (either topical or irrigation), may also promote a direct and specific effect on bone tissues that seems to stimulate both bone deposition and the osseointegration of implants [3,4,16,17,18,23].…”
Section: Discussionmentioning
confidence: 99%
“…Markers of bone metabolism, including serum alkaline phosphatase, procollagen 1 carboxylterminal propeptide, and deoxypyridinoline, increased significantly by GH administration [ 71 ]. Finally, GH powder application around dental implants placed immediately after tooth extraction enhances bone density and collagen fibers [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sustenta-se que esses fatores são uma alternativa ao uso de enxertos, exceto o autógeno, pois esses exerceriam a função de osteoindução nesses casos. Sugere--se o seu uso em reconstruções de grandes defeitos, inclusive 27 .…”
Section: Discussão Perspectivas Da Utilização Do Gh Na Odontologiaunclassified